The complete mitochondrial genome and phylogenetic analysis of Fusinus longicaudus (Gastropoda: Fasciolariidae). Issue 1 (2nd January 2019) - Feng, Jiantong; Fu, Zeqin; Guo, Yahong; Ye, Yingying; Li, Jiji; Guo, Baoying; Lü, Zhenming
Abstract: We first determined the complete mitochondrial genome of Fusinus longicaudus (Gastropoda: Fasciolariidae). The circular mitochondrial genome is 16, 319 bp in length, consisting of 13 protein-coding genes, 22 tRNA genes, and two ribosomal RNA genes. The nucleotide composition is 14.7% of C, 15.9% of G, 38.9% of T, and 30.5% of A. The control region with the length of 1029 bp is between tRNA Phe and COX3 genes. In 13 protein-coding genes, the nad4 gene starts with ATT, the other eleven genes start with ATG. For the stop codon, atp6, nad4l, nad5 and nad6 end with TAG, other 9 genes end with TAA. The phylogenetic tree was constructed based on 13 protein-coding genes of F. longicaudus and other 13 Neogastropoda species, Perna viridis as outgroup using the Neighbor-joining method, the result showed that F. longicaudus is most closely related to the Buccinidae. The mitochondrial genome would be helpful for the study of population genetic and phylogenetic analysis of the family Fasciolariidae.